Influence of competition on performance factors in under-19 soccer players at national league level - Izquierdo, J. M.; De Benito, A. M.; Araiz, G.; Guevara, G.; Redondo, J. C. (PLOS ONE, 2020)
The aim of this study was to analyse and quantify the acute effects of competition on several performance factors in under-19 male soccer players. To this end, 198 national league players (17.56 ± 0.78 years) performed various tests to measure jump capacity, kicking velocity and sprint times immediately pre-match (T1), at half-time (T2) and post-match (T3). Tests included kicking the ball to measure ball velocity (KICK), sprinting for 40 meters, timing the first 30 meters (30mACCEL), the last 10 meters (10mACCEL) and the total distance (40mACCEL), and performing countermovement jumps (CMJ). For subsequent analysis, the sample was divided into 5 playing positions: goalkeepers (n = 24), defenders (n = 51), midfielders (n = 36), wingers (n = 54) and forwards (n = 33). For all positions, we found a significant decline in performance (p<0.05) for kicking velocity (2.91% - 6.51%) and sprinting (0.44%-5.85%). For the CMJ, all positions except defenders presented a significant decline in performance that ranged from 1.5% to 4.56%. These findings highlight the need to individualise fitness training, taking into account the match needs and demands of the different playing positions in order to minimise the effects of match fatigue and accelerate post-match recovery.